2023
DOI: 10.2478/pcssr-2023-0007
|View full text |Cite
|
Sign up to set email alerts
|

Sustainability in Sport-Related Studies: A Non-Systematic Review to Increase the Sports Contribution to the 2030 Agenda

Abstract: This paper aims to identify all of the unexploited potentialities of sports activities with regard to sustainability by answering the following question: Considering the priorities that the 2030 Agenda identified with regard to sustainability, what does sport contribute to the process of transition towards a more sustainable global scenario? According to the European Union Council, sport and physical activity play a strategic role in the global challenge toward sustainability and achieving the 17 SDGs. The con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 133 publications
0
5
0
Order By: Relevance
“…On the other hand, literature reviews that explore the association between sustainability and football, noteworthy works include the review by Mabon [ 94 ] where an extensive analysis identifies four research areas: the impact of football on climate, the impact of weather on football, football as a driver of pro-environmental actions, and the relationship between football and carbon-intensive sports. Another review by Annesi et al [ 95 ] reveals that sport's contribution to the 2030 Agenda is strategically significant; however, there is a lack of consideration for SDGs in the sports literature.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, literature reviews that explore the association between sustainability and football, noteworthy works include the review by Mabon [ 94 ] where an extensive analysis identifies four research areas: the impact of football on climate, the impact of weather on football, football as a driver of pro-environmental actions, and the relationship between football and carbon-intensive sports. Another review by Annesi et al [ 95 ] reveals that sport's contribution to the 2030 Agenda is strategically significant; however, there is a lack of consideration for SDGs in the sports literature.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, high-performance athletes serve as role models for the whole world, especially for young people, so that other sustainable goals can also be addressed. As a result, numerous studies have demonstrated the enormous potential that sports activities offer for sustainability [17]. Olympic sports are a shining example of gender equality and sustainability, and via its athletes, they serve as a legendary source of motivation and aspiration for everyone [18].…”
Section: Introductionmentioning
confidence: 99%
“…the empowerment of women; Collison et al, 2019), it has recently come to be regarded as a means of promoting sustainable development. Sport management research has addressed various aspects of sustainability, such as the environmentally sustainable practices of sporting organisations (Trendafilova & McCullough, 2018); the contribution made by sport to social change and peace (Schulenkorf, 2010); and the role played by sport in health and well-being (Cunningham & Beneforti, 2005), but it is far from reaching saturation point (Annesi et al, 2023).…”
Section: Introductionmentioning
confidence: 99%